Didacticization of the press texts of the Galician Germans in DaF-lessons (Educational Dimension, 2020)
This paper deals with the authentic press texts of the Galician Germans from the “Deutsches Volksblatt f¨ur Galizien”, which was published in Lviv in the period between 1907–1918. A total of 240 newspaper editions were examined and 20 texts were written out of them. The article focuses on the didactization and use of historical press texts in foreign language teaching in higher education. It deals with the tasks and exercises that probably can be created from the historical press texts and also be used in German lessons at different learning levels. By applying the texts on the subject “History of Germans in Ukraine” new linguistic and cultural skills will be acquired by learners. The historical press texts fulfill an informative function and thus contribute to conveying the important historical events of the country to the learners. Working with the authentic press texts in foreign language lessons enables the expansion of intercultural competence, promotes critical thinking and focuses on expanding language skills. In choosing the historical press texts following would be considered: the texts should be information-based, contain something new and be of interest to the students; the texts should pursue an achievable goal; the texts should be suitable for the student’s level of learning. In this paper information-based, not long texts from the fields of society, science or world politics were chosen. A total of 15 texts were didactized. At least 10 tasks were worked out for each text. They are right/wrong — exercises, multiple choice exercises, search exercises, fill-in-the-blanks-exercises, reproductive exercises, chain exercises, role playing, etc. The press texts of the Galician Germans proved to be a rich source of information about the life of the Germans in the region and can also be used in German lessons in addition to the main textbook. In this way, the Ukrainian learners learn about the history of Germans from the primary sources and thus acquire intercultural and regional study skills